2006
DOI: 10.5194/angeo-24-2201-2006
|View full text |Cite
|
Sign up to set email alerts
|

Reconfiguration of polar-cap plasma in the magnetic midnight sector

Abstract: Abstract. Radio tomography and the EISCAT and Super-DARN radars have been used to identify long-lived, highaltitude, cold plasma in the antisunward convective flow across the polar cap. The projection of the feature to later times suggests that it was reconfigured in the Harang discontinuity to form an enhancement that was elongated in longitude in the sunward return flow of the high-latitude convection pattern. Comparison with a tomographic image at a later time supports the interpretation of a polar patch be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 29 publications
0
10
0
1
Order By: Relevance
“… Pryse et al [2004] found that photoionization and convection were also the source of polar cap plasma found near local magnetic noon but separate from the main body of photoionization. In a later study in the dusk‐midnight sector, Pryse et al [2006b] used tomography and SuperDARN convection patterns to numerically track a polar patch from the anti‐sunward convection flow, through the Harang discontinuity and into sunward flow, where it formed a boundary blob.…”
Section: Discussionmentioning
confidence: 99%
“… Pryse et al [2004] found that photoionization and convection were also the source of polar cap plasma found near local magnetic noon but separate from the main body of photoionization. In a later study in the dusk‐midnight sector, Pryse et al [2006b] used tomography and SuperDARN convection patterns to numerically track a polar patch from the anti‐sunward convection flow, through the Harang discontinuity and into sunward flow, where it formed a boundary blob.…”
Section: Discussionmentioning
confidence: 99%
“…Patches convecting into the auroral oval have been shown to be associated with substorm onset [Lyons et al, 2011;Nishimura et al, 2013Nishimura et al, , 2014Shi and Zesta, 2014]. In the auroral oval, they are termed auroral blobs [Tsunoda, 1988;Crowley et al, 2000;Lorentzen et al, 2004;Pryse et al, 2006]. Several types of auroral blobs are referred to in literature, namely, boundary blobs, subauroral blobs, and auroral blobs [e.g., Crowley et al, 2000].…”
Section: Polar Cap Patch Activitymentioning
confidence: 99%
“…The modeled and observed values at the final location were compared and agreed within experimental uncertainties. PLASLIFE had also been used previously to assist in the interpretation of observations in the nightside ionosphere [ Pryse et al , 2006; Wood et al , 2008].…”
Section: Instrumentation and Simulationmentioning
confidence: 99%
“… Robinson et al [1985] modeled a patch drifting out of the polar cap, which was reconfigured to form a boundary blob in the nightside auroral oval. Subsequent observations have shown patches drifting out of the polar cap [ Pedersen et al , 2000] and being reconfigured to form a boundary blob [ Pryse et al , 2006].…”
Section: Introductionmentioning
confidence: 99%